The role of primary care in promoting children's physical activity. Issue 1 (10th November 2008) - Huang, J S; Sallis, J; Patrick, K
Abstract : Regular physical activity enhances health during childhood and adolescence and is important in setting the stage for participation in physical activity across the lifespan. Physician–patient interactions during childhood and adolescence provide important opportunities for clinicians to influence physical activity behaviours. This article reviews current physical activity recommendations for youth and the wide range of health benefits provided to youth from engaging in regular physical activity. It also outlines a practical counselling model, the 5As approach, that can guide clinical counselling for physical activity, and reviews how an increasingly important model of practice organisation, the Care Model, can be used to promote physical activity in children and adolescents. Family, social and environmental influences on child and adolescent physical activity are also addressed.